(untitled) (Journal of Engineering, 2011)
Low bearing capacity of weak soil under shallow footings represents one of construction problems. Kaolin with water content converges to liquid limit used to represent the weak soil under shallow footing prototype. On the other hand, fly ash, which can be defined as undesirable industrial waste material, was used to improve the bearing capacity of the soft soil considered in this research. The soft soil was prepared in steel box (36×36×25) cm and shallow square footing prototype (6×6) cm were used .Group of physical and chemical tests were conducted on kaolin and fly ash. The soft soil was improved by a bed of compacted fly ash placed under the footing with dimensions equal to that of footing but with different depth ratios. The results show that there is a noticeable improvement in the behavior of footing when improved by compacted fly ash. The improvement showed a decrease in settlement and increase in bearing capacity. The improvement ratio in bearing capacity was calculated by comparing the ultimate bearing capacity value when testing the kaolin alone with its value of kaolin improved with compacted fly ash at the same value of eccentricity. It is important to note that eccentricity values were chosen according to the rule of middle third of footing base(i.e.,e≤B/6). The improvement ratio was about (130%) in average value, that represent a good ratio of improvement